Risk and impact of the educational malpractice and negligence in the delivery of higher education / Rosmi Yuhasni Mohamed Yusuf - Mohamed Yusuf, Rosmi Yuhasni (2007)
Educational malpractice and negligence are unexplored territory insofar as civil tort liability in Malaysia is concerned. Professional liability for substandard work has been widely recognised with precedents passed from one case to another but professional liability in respect of substandard delivery of higher education by lecturers and educational service providers are merely illusive. Lecturers' legal liability for damage suffered by students because of incompetent or careless teaching is, however, possible if references are made to a few number of decided case law involving teachers and schools in other Commonwealth countries -and the US included. Educational negligence is a topic needed to be thoroughly considered as this area of professional liability has emerged as a movement towards accountability for educational outcomes. This discussion paper is an attempt to explore the possibility of negligence suit by students as a result of incompetence and breach of care of lecturers in delivering a proper lecturing standard expected from a reasonable lecturer.